Recent progress in and prospects for supercapacitor materials based on metal oxide or hydroxide/biomass-derived carbon composites - Ruiz-Montoya, Jose G. (2021)
This work was supported by Peruvian government agencies CONCYTEC and FONDECYT/World Bank (contract 026-2019 FONDECYT-BM-INC.INV) and the Sao Paulo Research Foundation (FAPESP) through the fellowships granted to J. M. G. (FAPESP 2018/16896-7).